Neuerungen in Herstellung und Verwaltung von Schriftgut im ordenszeitlichen Preußen bis zum Beginn des 13-jährigen Krieges - Heckmann, Dieter (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2024)
Innovations in the production and administration of documents in Prussia during the Teutonic Order’s time until the beginning of the Thirteen Years’ War If innovations in the administration of records may be regarded as the results stemming from impulses either beyond the specific reasons for writing, or beyond the need to improve clarity, then at least four of them can be recognized for the Prussian period of the Teutonic Order. These were the registration of letters in full text, the “official” translation, the recording of the pound customs receipts and the creation of collections of formulas adapted to the needs of writers, which contributed to the standardization of the administrative and legal area in Prussia. This article argues that these changes can usually be associated with the increasing employment of public notaries in the sovereign or municipal administrations of late medieval Prussia.